2020
DOI: 10.1111/den.13631
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristic of esophageal cancer without lugol‐voiding lesions in the background esophagus

Abstract: Lugol chromoendoscopy is useful for the detection of early esophageal squamous cell cancer (ESCC). Multiple lugol-voiding lesions (LVLs) on lugol chromoendoscopy are associated with a very high risk of multiple cancers arising in the esophagus. Due to the widespread use of narrow band image technology in many institutions, esophageal cancer without LVLs in the background esophagus is sometimes detected. This retrospective study aims to clarify the clinical characteristic of esophageal cancer without LVLs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The authors suggested a genetic predisposition to carcinogenesis. Kuwabara et al [25] reported that esophageal cancer without LVLs in the background esophagus likely has a longitudinal shape with jaggy like thunder, which was named “thunder-shaped LVLs.” They focused on the relationship between development of ESCC and reflux esophagitis in patients with no LVLs (LVL grade A) and assumed that persistent esophageal reflux and retention of refluxed food may contribute to the development of ESCC. Although the present study showed no statistically significant difference in the frequency of erosive esophagitis between the very low-risk group and the any-risk group, the ratio of symptomatic patients was significantly higher in the very low-risk group; this may reflect the difference in the frequency of esophageal reflux between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested a genetic predisposition to carcinogenesis. Kuwabara et al [25] reported that esophageal cancer without LVLs in the background esophagus likely has a longitudinal shape with jaggy like thunder, which was named “thunder-shaped LVLs.” They focused on the relationship between development of ESCC and reflux esophagitis in patients with no LVLs (LVL grade A) and assumed that persistent esophageal reflux and retention of refluxed food may contribute to the development of ESCC. Although the present study showed no statistically significant difference in the frequency of erosive esophagitis between the very low-risk group and the any-risk group, the ratio of symptomatic patients was significantly higher in the very low-risk group; this may reflect the difference in the frequency of esophageal reflux between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior wall of the mid-thoracic esophagus is where the refluxed stomach acid and contents are retained in the supine position. 35 Therefore, based on morphology and location, it is speculated that retention of refluxed gastric acid and stomach contents in the posterior wall of the mid-thoracic F I G U R E 3 Alteration profiling of 32 lesions in the NDNS group and 37 in the DS group. The main panels contain the mutation patterns of 40 genes with more than 4% somatic mutations from 32 and 37 lesions in the NDNS and DS groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the characteristic endoscopic finding of ESCC in nondrinking, nonsmoking women was longitudinal morphology with keratinization of the posterior wall of the mid‐thoracic esophagus. The posterior wall of the mid‐thoracic esophagus is where the refluxed stomach acid and contents are retained in the supine position 35 . Therefore, based on morphology and location, it is speculated that retention of refluxed gastric acid and stomach contents in the posterior wall of the mid‐thoracic esophagus led to the occurrence of ESCC in nondrinking, nonsmoking women.…”
Section: Discussionmentioning
confidence: 99%